Estimated age of first exposure to contact sports and neurocognitive, psychological, and physical outcomes in healthy NCAA collegiate athletes: A cohort study - Caccese, B.; Bodt, A.; Iverson, L.; Kaminski, W.; Bryk, K.; Oldham, J.; Broglio, S. P.; McCrea, M.; McAllister, T.; Buckley, A. (Sports Medicine, 2020)
Background: Collegiate football players who started playing tackle football before age 12 years did not show worse neuropsychological test performance than those who started playing tackle football after age 12 years. It is unknown if beginning other contact sports, such as lacrosse, at a younger age is associated with worse neurocognitive performance, greater psychological distress, or worse postural stability in collegiate student athletes. Objective: The purpose of this study was to examine the association between estimated age of first exposure (eAFE) to repetitive head impacts (RHI) and these outcome measures in collegiate student athletes. Methods: 1891 female and 4448 male collision/contact (i.e., football, ice hockey, lacrosse, wrestling, soccer) and non-contact (i.e., golf, rifle, rowing/crew, swimming, tennis) sport athletes completed baseline testing, including the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT), Brief Symptom Inventory 18 (BSI-18), and Balance Error Scoring System (BESS). Results: For women, the eAFE-by-sport interaction was associated with ImPACT Verbal Memory and Visual Memory, whereby earlier eAFE to contact sports was associated with higher composite scores (B = - 0.397, B = - 0.485, respectively). For men, the eAFE-by-sport interaction was associated with BSI-18 Depression and Global Severity Index and symptom severity scores, whereby earlier eAFE to football was associated with lower psychological distress and symptom severity [Depression, Exp(B) = 1.057; Global Severity Index, Exp(B) = 1.047; Symptom Severity, Exp(B) = 1.046]. Parameter estimates were small suggesting these results may have minimal practical relevance. Conclusion: Findings suggest that RHI during early adolescence is unrelated to brain health as measured by these specific outcome measures in collegiate student athletes.